Pengaruh Financial Distress terhadap Auditor Switching - Syafrita Ridha Ginting; Slamet Sugiri (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2025)
This study aims to examine whether certain financial indicators, previously identified as strong predictors of financial distress, influence auditor switching. The indicators analyzed are return on total assets, net profit on total assets, earnings per share, and cash flow per share. The sample consists of 37 financially distressed companies listed on the Indonesia Stock Exchange, identified using the Altman Z